Исследования храма Христа Спасителя на г. Бойка в Крыму в 2008 г. - Мыц, В.Л.; Юрочкин, В.Ю. (Археологічні дослідження в Україні, 2009)
The paper is devoted to the results of protective archaeology research at the temple of the Christ the Saviour of honourable Poyka at the mount Boyka in the Crimea in 2008. The architecture and stratigraphy of the monument were studied, and an interesting find was discovered in its ancient part.